Applications and Limitations of Oxime‐Linked "Split PROTACs". (28th July 2022) - Gui, Weijun; Kodadek, Thomas
Abstract: Proteolysis targeting chimeras are of keen interest as probe molecules and drug leads. Their activity is highly sensitive to the length and nature of the linker connecting the E3 Ubiquitin Ligase (E3 Ubl) and target protein (TP) ligands, which therefore requires tedious optimization. The creation of "split PROTACs" from E3 Ubl and TP ligands modified with residues suitable for them to couple when simply mixed together would allow various combinations to be assessed in a combinatorial fashion, thus greatly easing the workload relative to a one‐by‐one synthesis of many different PROTACs (proteolysis targeting chimeras). We explore oxime chemistry here for this purpose. We show that PROTAC assembly occurs efficiently when the components are mixed at a high concentration, then added to cells. However, in situ coupling of the TP and E3 Ubl ligands is inefficient when these units are added to cells at lower concentrations. Abstract : The activity of a proteolysis targeting chimera is highly dependent on the length and nature of the linker connecting the two component ligands. We explore the utility of using an oxime ligation to rapidly examine all the activity of "split PROTACs" created from collections of aldehyde‐ and alkoxyamine‐functionalized pieces. Advantages and limitations of this approach are discussed.